The relationship between bullying and burnout: An empirical investigation of Turkish professional football players - Yildiz, S. M. (Sport, Business and Management, 2015)
Purpose: The purpose of this paper is to investigate the relationship between bullying and burnout and its effect on professional football players. Although the effects of both bullying and burnout have been studied in different contexts, the effects of these constructs have not been fully examined among professional football players in culturally different environments.